Faktor-faktor yang Mempengaruhi Niat Melapor Insiden Keselamatan Pasien - Iskandar, Heru; Wardhani, Viera; Rudijanto, Achmad (Universitas Brawijaya, Indonesia, 2016)
Data indicate low patient safety incident report (PSI) at the X hospital (0.22%) when compared to theoretical prediction which is 10% of hospital admission. The PSI report is one of quality control method to prevent the incident recurrence. This study identify that the intention to report PSI is influenced by individual factors i.e. age, gender, working period, position, education level, employment status as well as organizational factors i.e. knowledge, patient safety culture, reporting system and response of the report. This study aimed to identify the role of individual and organizational factors on the intention to report PSI in all cases severity level (mild, moderate or severe). A structured questionnaire developed form previous research were distributed to 283 respondents (184 medical staff and 99 non-medical staff). A logistic regression analysis was performed to test the hypothesis. The level of respondents'perceptions of organizational factors are moderate, including knowledge of PSI report, patient safety culture, reporting system and response of the report. About 39.92% of the respondents did not know how to report the PSI. The majority of respondents tend to report all PSI, either mild, moderate or severe cases. Individual and organizational factors simultaneously did not predict the intention to report PSI. Partially only organizational factors i.e. knowledge, patient safety culture and manager response to the report significantly predict the intention to report moderate case PSI (α <0.05). Organizational factors play a role in building a reporting culture, therefore the hospital need to put more effort in improving the staff knowledge, safety culture and provide adequate response to PSI report.